The Function of Risk, Adaptability, Dependability, Completeness, and Simplicity for Myhero Application Users at PT Henan Putihrai Asset Management Employing the Delone McLean Method - Irma Selliamanik; Irnawasih; Markonah Markonah; Yohanes Ferry Cahaya; Suryanto Suryanto (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2026)
This research aims to analyze the factors influencing users of the MyHero application at PT Henan Putihrai Asset Management using the Delone McLean approach. The design of this research uses a quantitative research method. This research uses primary data, and the data used in this study were obtained from the distribution of electronic questionnaires to investors who invest using the MyHero application. The data for this research were processed using SPSS Version 22. In this study, the sample used consisted of 370 respondents who had previously used the MyHero application. The results of this study partially show that the variables of Risk, Flexibility, Reliability, Responsiveness, Completeness, and Ease of Information significantly affect the Use of the MyHero Application. Recommendation. Increase risk, flexibility, reliability, responsiveness, completeness, and ease of information so that the decision to use the MyHero Application improves.